Root cause of groundwater colouration in coastal districts of Bangladesh: findings from a preliminary study. Issue 1 (1st January 2021) - Kabir, Ahammadul; Ahmed, Alauddin; Rahman, Mizanur; Md Taimur, Ibrahim; Ahmad, Shamsuddin; Khan, Mohammed Mahmud; Saifur Rahman, Mohammad; Noor, Abdun
ABSTRACT: The study characterises the straw-colour in groundwater of coastal areas of Bangladesh. The study design was exploratory to have a better understanding of straw colouration. Findings indicate that the straw-colour is an entirely true colour in Alpha-Hazen Scale due to dissolved organic components tannin/lignin with different functional groups. The concentration of different parameters of water influences the intensity of the colour. The intensity of straw-colour has a significant positive correlation with depth and has spatial variation within the study sites. Borehole sediment sample analysis confirms the presence of organic particles. People who drink straw-coloured water in Barguna Upazila for a relatively more extended period show signs and symptoms of kidney-related disorders. A further detailed study with chemical analysis of straw-coloured water by NMR and GCMS should help identify the exact structure of the organic elements and public health vulnerabilities that a cohort study should firm.